2018
DOI: 10.1186/s12883-018-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-familial phenotypic heterogeneity in a Sudanese family with DARS2-related leukoencephalopathy, brainstem and spinal cord involvement and lactate elevation: a case report

Abstract: BackgroundLeukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL, OMIM #611105) is a genetic disease of the central nervous system characterized by lower limb spasticity, cerebellar ataxia and involvement of the dorsal column. The disease is caused by mutations in the DARS2 gene but has never been reported in sub-Saharan Africa so far.Case presentationTwo siblings, aged 18 years and 15 years, from a consanguineous family presented with pyramidal signs and symptoms since infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…The older sibling was diagnosed due to the diagnosis of the younger siblings. 9 In our study, both siblings with DARS2 deficiency had global developmental delay within the first year of life. Younger sibling presented with motor regression after a viral infection at the age of 6 months.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The older sibling was diagnosed due to the diagnosis of the younger siblings. 9 In our study, both siblings with DARS2 deficiency had global developmental delay within the first year of life. Younger sibling presented with motor regression after a viral infection at the age of 6 months.…”
Section: Discussionsupporting
confidence: 45%
“…Two younger siblings had infantile onset global developmental delay and the oldest sibling presented with a mild lower limb spasticity at the age of 20 years. The older sibling was diagnosed due to the diagnosis of the younger siblings . In our study, both siblings with DARS2 deficiency had global developmental delay within the first year of life.…”
Section: Discussionmentioning
confidence: 59%
“…One study of DARS2 missense mutations in LBSL patients has been shown that the mutations have variable effects on the enzyme activity, protein expression, localization, and dimerization of protein [20]. Another report observed that the same compound heterozygous mutations presented with phenotypic variability, from a healthy individual to disabled patients, within a family with DARS2-related LBSL [21]. Three siblings with LBSL who presented with nystagmus, slurring of speech, muscle tonus abnormality, ataxic gait, hypo or hyperreflexia, tremor, and mental retardation caused by DARS2 mutation were considered to display a severe form of LBSL [22].…”
Section: Discussionmentioning
confidence: 99%
“…In general, earlier onset of symptoms predicted more severe neurological deterioration in the first decade after disease onset [22]. Case reports of affected siblings have shown that both mild and severe disease phenotypes can manifest even when the DARS2 mutations are identifical [41, 42].…”
Section: Lbsl Patterns Of Disease Progressionmentioning
confidence: 99%